Experimental measurements versus linear stability analysis for primary instability of stratified two-phase flows in a square rectangular duct. (August 2022) - Nezihovski, Yakov; Gelfgat, Alexander; Ullmann, Amos; Brauner, Neima
Highlights: Stability of stratified two-phase pressure driven flow in a square pipes is experimentally studied. The results are obtained by a partially novel non-intrusive technique. A wide range of the two superficial velocities is explored. The experimental results are successfully compared with numerical predictions. Abstract: The onset of the primary instability of two-phase stratified flow in a square duct was studied experimentally. Measurements were carried out by a specially designed fully non-intrusive technique. Critical values of the two superficial velocities corresponding to the primary instability of air-water stratified flows in a square duct were measured and successfully compared with the computationally predicted stability diagram. Along with the good quantitative agreement between the experimentally measured and numerically predicted critical superficial velocities, a qualitative agreement was obtained between predicted and measured frequencies of the critical perturbations.